2004
DOI: 10.1111/j.1365-3180.2004.00405.x
|View full text |Cite
|
Sign up to set email alerts
|

Joint action of amino acid biosynthesis‐inhibiting herbicides

Abstract: The joint action of binary mixtures of the amino acid biosynthesis-inhibiting herbicides glyphosate, glufosinate-ammonium, metsulfuron-methyl and imazapyr was assessed in pot experiments applying the Additive Dose Model (ADM). Plants of Sinapis arvensis or S. alba were sprayed with seven doses of the herbicides alone and binary fixed-ratio mixtures of the four herbicides. In total, 73 binary mixtures were studied in six separate experiments. Mixtures of glyphosate and glufosinate-ammonium were less phytotoxic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
48
0
2

Year Published

2006
2006
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(53 citation statements)
references
References 25 publications
3
48
0
2
Order By: Relevance
“…Amidosulfuron is recommended for use on wheat (winter and spring) and spring barley for the control of broad-leaved weeds. The mechanism of sulfonylureas action and toxicity to higher terrestrial plants is well studied (Duke, 1990;Kudsk, Mathiassen, 2004;Binder et al, 2007), although relatively little is known about the toxic effects of these herbicides on non-target aquatic organisms. Several studies have shown that sulfonylurea herbicides negatively affect growth, physiology and reproduction of non-target aquatic plant (Frankart et al, 2003;Eullaffroy et al, 2007;Fairchild et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Amidosulfuron is recommended for use on wheat (winter and spring) and spring barley for the control of broad-leaved weeds. The mechanism of sulfonylureas action and toxicity to higher terrestrial plants is well studied (Duke, 1990;Kudsk, Mathiassen, 2004;Binder et al, 2007), although relatively little is known about the toxic effects of these herbicides on non-target aquatic organisms. Several studies have shown that sulfonylurea herbicides negatively affect growth, physiology and reproduction of non-target aquatic plant (Frankart et al, 2003;Eullaffroy et al, 2007;Fairchild et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…The observed ED 90 doses were plotted on the graph and compared to the ADM isoboles. Points above the isoboles indicate that the joint action of a mixture is lower than predicted by ADM, while points below the isoboles indicate a joint action higher than predicted by ADM (Kudsk & Mathiassen, 2004).…”
Section: Joint Action Modelmentioning
confidence: 99%
“…with the herbicide mixtures originate from up to seven separate experiments, it was necessary to standardize the x-and y-axes so that the ED 90 doses of the herbicides applied separately were always fixed to 1 (Kudsk & Mathiassen, 2004).…”
Section: Joint Action Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Mixing certain chemicals or herbicides with glyphosate has been shown to affect glyphosate efficacy (Kudsk & Mathiassen, 2005;Koger et al, 2007). O 'Sullivan & O'Donovan (1980) observed that a glyphosate in tank mixture with dicamba and 2,4-D reduced the phytotoxicity of glysophate threshold rates on grasses.…”
Section: Introductionmentioning
confidence: 99%